On unearned privilege in clinical practice. (February 2021) - Little, John D
Objective: To explore what it might mean to be a white psychiatrist working in a white culture. Conclusions: Inequalities and power imbalances are maintained by person-blaming and the invisibility of structural inequality. Opportunities to recognise the effects of being privileged and working within a medical culture that compounds such inequality may be squandered without curiosity and action.